Reverse placement of a double J ureteral stent improves lower urinary tract symptoms - Goksel Bayar; Abdulmecit Yavuz; Yilmaz Ofluoglu; Caglar Yildirim (BMC Urology, 2025)
Abstract Objective To investigate the clinical efficacy and patient-reported discomfort associated with traditional versus reverse placement of double-J ureteral stents (DJUS) in patients undergoing ureteroscopic stone removal. Materials and methods This prospective, randomized, single-center, one blinded, controlled study. In the control group, the double-J stent was placed with its upper end facing laterally (towards the kidney) and its lower end facing medially (towards the bladder trigone), while in the study group, the reverse was done in a mirror manner. Patients in the study group were further subdivided based on the orientation of the upper and lower tips of the stent (B1: upper medial/lower lateral, B2: both medial, B3: both lateral). Patient discomfort was assessed using the Turkish version of the Ureteral Stent Symptom Questionnaire (T-USSQ), and secondary outcomes included postprocedural hydronephrosis, hematuria, and urinary tract infection. Results A total of 120 patients were included and 60 patients to each the control and study groups. Forty patients were included in group B1, 8 in B2 and 12 in B3. The reverse placement group (Group B) reported significantly lower USSQ (p < 0.05) and reduced analgesic use compared to the control group. Midline crossing of the stent was significantly less frequent in the study group (11.7% vs. 30%; p = 0.013). Subgroup analysis revealed that the B1 and B3 groups had significantly lower analgesic usage and symptom scores compared to the control group, while the B2 group reported higher hydronephrosis and symptom scores. Conclusion Reverse placement of DJUS, particularly when both stent ends are laterally positioned, may reduce stent-related discomfort. There is a need for a new stent design with both ends facing laterally, tentatively named “ipsi-DJUS”. Trial registration Turning the tip of the stent upside down may ease urinary symptoms” is now listed on the ISRCTN registry with study registration number ISRCTN17937257 (Date of registration: 22/10/2024). Retrospectively registered.